One Minute Preceptor Model – place or to replace - Tambolkar, Sampada; Chavan, Sanjay; Agarkhedkar, Sharad; Salunkhe, Shradha; Patil, Manojkumar; Giri, Purushottam (Indian Journal of Community Health, 2023)
Introduction: Neher's 1992 One Minute Preceptor Model (OMP) offers a concise teaching approach based on five micro skills. Its acceptance led to research on efficacy, with a critical factor being the teacher's skill. In medical education, where small group teaching prevails, understanding factors influencing teaching effectiveness is crucial. Methods: Conducted at Dr. D Y Patil Medical College, the mixed-methods interventional study involved 32 Postgraduate Students and 4 Professors. A randomized controlled trial and qualitative interviews assessed the impact of OMP on teaching efficacy and gathered teachers' experiences. Results: Quantitative analysis revealed varied preferences among teachers for OMP and traditional methods, emphasizing the importance of teacher choice. Thematic analysis of qualitative interviews highlighted perceptions favouring OMP for efficiency and traditional methods for foundational teaching. Conclusion: An approach, to accommodate different teaching preferences, can enhance overall educational outcomes.